2018
DOI: 10.1038/s41467-017-02748-x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental enrichment increases transcriptional and epigenetic differentiation between mouse dorsal and ventral dentate gyrus

Abstract: Early life experience influences stress reactivity and mental health through effects on cognitive-emotional functions that are, in part, linked to gene expression in the dorsal and ventral hippocampus. The hippocampal dentate gyrus (DG) is a major site for experiencedependent plasticity associated with sustained transcriptional alterations, potentially mediated by epigenetic modifications. Here, we report comprehensive DNA methylome, hydroxymethylome and transcriptome data sets from mouse dorsal and ventral DG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
101
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(119 citation statements)
references
References 60 publications
11
101
0
Order By: Relevance
“…48 Pregnancy swimming also increased hippocampal BDNF levels in the rat offspring, which contributed for smaller lesions, preservation of white matter tracts, improved delay in reflex maturation as well as spatial memory deficits in rats that suffered neonatal hypoxia-ischemia. 50 Environmental enrichment after prenatal stress decreases depressive-like behaviors and fear, and improves cognitive deficits, as well as increases spine density, granular cells, and BDNF in the hippocampus of the offspring. 50 Environmental enrichment after prenatal stress decreases depressive-like behaviors and fear, and improves cognitive deficits, as well as increases spine density, granular cells, and BDNF in the hippocampus of the offspring.…”
Section: Possible Factors For Reversibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…48 Pregnancy swimming also increased hippocampal BDNF levels in the rat offspring, which contributed for smaller lesions, preservation of white matter tracts, improved delay in reflex maturation as well as spatial memory deficits in rats that suffered neonatal hypoxia-ischemia. 50 Environmental enrichment after prenatal stress decreases depressive-like behaviors and fear, and improves cognitive deficits, as well as increases spine density, granular cells, and BDNF in the hippocampus of the offspring. 50 Environmental enrichment after prenatal stress decreases depressive-like behaviors and fear, and improves cognitive deficits, as well as increases spine density, granular cells, and BDNF in the hippocampus of the offspring.…”
Section: Possible Factors For Reversibilitymentioning
confidence: 99%
“…49 Experimental environmental enrichment has a series of beneficial effects associated with neuroplasticity mechanisms, increasing hippocampal volume, and enhancing dorsal dentate gyrus-specific differences in gene expression. 50 Environmental enrichment after prenatal stress decreases depressive-like behaviors and fear, and improves cognitive deficits, as well as increases spine density, granular cells, and BDNF in the hippocampus of the offspring. 51 Environmental enrichment also improves learning and memory deficits associated with neonatal hypoxia-ischemia, through an increased dendritic spine density in the hippocampus of adult rats.…”
Section: Possible Factors For Reversibilitymentioning
confidence: 99%
“…Interestingly, Yun et al recently found that NLY01, an agonist of Glucagon-like peptide-1 receptor (GLP1R), can improve the cognitive function and prolong life of PD mouse model by preventing the transformation of astrocytes into A1 type (Yun et al, 2018). Guo et al (2014) injected a retrovirus under the control of GFAP promoter in adult mouse cortex to specifically express NeuroD1, which is essential for adult neurogenesis (Gao et al, 2009;Zhang et al, 2018), in activated astrocytes. It is worth to mention that retroviruses only infect dividing cells such as progenitor cells or reactive glial cells (Ambrosius et al, 2017;Zhao, Teng, Summers, Ming, & Gage, 2006).…”
Section: Subtypes Of Activated Astrocytesmentioning
confidence: 99%
“…Epigenetic marks like DNA methylation enable dynamic regulation of gene expression throughout the life of a neuron 20,21 . In the brain, divergent DNA methylation signatures facilitate the functional specialization of neurons and brain subregions [22][23][24] . During early development, hemispheric asymmetry in DNA methylation contributes to the lateralization of nervous system organization, which affects hemisphere dominance for handedness, cognitive processes, and language [25][26][27] .…”
Section: Introductionmentioning
confidence: 99%